2009
DOI: 10.1248/bpb.32.767
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Lectins Involved in Folding and Transport in the Endoplasmic Reticulum

Abstract: Glycosylation is a highly sophisticated post-translational modification of proteins that occurs in the endoplasmic reticulum (ER) and the Golgi apparatus. The vital biological functions served by protein glycosylation can be separated into two types. The first is the role of glycosylation in the extracellular environment, where a variety of sugar chains participate in protein secretion and stability, cell-cell adhesion and signaling, innate immunity, embryogenesis, and morphogenesis. Another role is in quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…LMAN2L, also named VIPL, is a transmembrane protein located at the ER (figure 3E),29 which plays a role in the quality control of glycoproteins. It functions as a cargo receptor for glycoproteins and is expected to regulate the exchange of folded and misfolded glycoproteins for transport to the Golgi or to the ubiquitin-proteasome pathway, respectively 30 31. Different studies have shown that the substitution of a single amino acid can switch the sugar-binding affinity32 and thereby impair protein function.…”
Section: Discussionmentioning
confidence: 99%
“…LMAN2L, also named VIPL, is a transmembrane protein located at the ER (figure 3E),29 which plays a role in the quality control of glycoproteins. It functions as a cargo receptor for glycoproteins and is expected to regulate the exchange of folded and misfolded glycoproteins for transport to the Golgi or to the ubiquitin-proteasome pathway, respectively 30 31. Different studies have shown that the substitution of a single amino acid can switch the sugar-binding affinity32 and thereby impair protein function.…”
Section: Discussionmentioning
confidence: 99%
“…CRDs in vertebrate lectins can be classified in families with well‐established types: intracellular lectins (calnexin family, M‐type, L‐type, and P‐type, located in luminal compartments of the secretory pathway and function in the trafficking, sorting, and targeting of glycoproteins) , and extracellular lectins (C‐type, R‐type, siglecs, and galectins) . The latter are either secreted into the extracellular matrix or body fluids or localized to the plasma membrane, and mediate a range of functions including cell adhesion and signaling, pathogen recognition, and glycoprotein clearance . Interestingly, the galectin family of lectins in animals are also high‐abundance cytoplasmic proteins, as large pools of these proteins are soluble in the cytoplasm, probably as precursors of those later secreted to the pericellular matrix [1, 43].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other glycoproteins, early glucose trimming of the newly attached Glc 3 Man 9 GlcNAc 2 N -glycan core facilitates proper interactions with the lectin chaperones calnexin and calreticulin, which are involved in the chaperone-assisted protein folding and assembly pathway. Additional lectins can also contribute to this protein quality control pathway and transport from ER to Golgi [15]. Following correct protein folding and molecular assembly (i.e., β2-microglobulin and peptide antigen binding in the case of MHCIa), the N -glycan is further modified as it moves through the Golgi.…”
Section: Roles For Protein N-glycosylationmentioning
confidence: 99%